Simultaneous Determination of Twelve Tetrahydrocorticosteroid Glucuronides in Human Urine by Liquid Chromatography/Electrospray Ionization-Linear Ion Trap Mass Spectrometry - Ikegawa, Shigeo; Hasegawa, Maki; Okihara, Rika; Shimidzu, Chikara; Chiba, Hitoshi; Iida, Takashi; Mitamura, Kuniko (Analytical chemistry (Washington), 2009)
A liquid chromatography/electrospray ionization (ESI)-mass spectrometry (MS) method for the direct determination of 12 tetrahydrocorticosteroid glucuronides in human urine has been developed. The analytes were 3- and 21-monoglucuronides of tetrahydrocortisol, tetrahydrocortisone, tetrahydro-11-deoxycortisol, and their 5α-stereoisomers. The mass spectrometric behaviors of these glucuronides in negative-ion ESI-MS/MS revealed the production of intense, structure-specific product ions within the same group of glucuronides. Regioisomeric glucuronides could be distinguished by collision-induced dissociation and tandem mass spectrometry. Using a linear ion trap instrument operating in the negative-ion mode and by monitoring the transition ions of [M − H]− → [M − H − CH2O]− for 3-monoglucuronides and [M − H]− → [M − H − CH2OG]− for 21-monoglucuronides, a sensitive and specific assay was developed. Initial steps in the assay were a simple solid-phase extraction and the addition of [9,12,12,21,21-d 5]-tetrahydrocortisone-3-glucuronide (prepared by enzyme-assisted synthesis) as an internal standard. The method was applied to determine the 12 tetrahydrocoticosteroid glucuronides in urine from healthy subjects and from patients with excessive cortisol production. The method described here appears to be useful for clinical and biochemical studies.